IoT-Enabled Platform for Sustainable Used Cooking Oil Collection in Culinary SMEs and Restaurants - Aska Juta Tafrika Putra; Gunawan, Alberto Donny; Susanto, Novella; Abdul Rohman (International Journal of Applied Management and Business, 2026)
Purpose – This paper aims to design an innovative business model through a sustainable used cooking oil (UCO/minyak jelantah) management platform as an alternative solution to improve the effectiveness of UCO disposal and collection among restaurants and culinary SMEs. The study is motivated by the generally low adoption of proper UCO management practices in Indonesia, which contributes to environmental pollution and potential public health risks. Methodology/approach – This research applies the Business Model Canvas (BMC) to develop a technology-enabled solution, namely Throily, an ecosystem that combines IoT-based automatic volume recording with a digital application that connects SMEs and restaurants with UCO collectors to support safer and more transparent collection processes. Findings – The proposed Throily business model offers a clear value proposition: safer handling, improved operational efficiency, and transparent UCO collection, while also providing financial incentives for participating businesses. The primary target segment consists of restaurants and culinary SMEs in West Jakarta that generate UCO regularly yet lack efficient storage and pick-up systems. Financially, the model demonstrates sustainability potential through diversified revenue streams, including device sales, subscription programs, in-app advertising, and collaborations/partnerships. Novelty/value – By integrating IoT-enabled tracking with a digital marketplace and community-based collection ecosystem, Throily strengthens circular economy implementation and offers a scalable approach to reducing improper UCO disposal while generating measurable environmental and socio-economic benefits.